2005
DOI: 10.1189/jlb.0105015
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional profiling of human proinflammatory type-1 and anti-inflammatory type-2 macrophages in response to microbial antigens and IFN-γ- and CD40L-mediated costimulation

Abstract: Macrophages (Mphi) comprise a heterogeneous population of cells with various immune and homeostatic functions. Recently, we have described type-1 and type-2 human monocyte-derived Mphi subsets. Although both support outgrowth of intracellular mycobacteria, Mphi-1 secretes interleukin (IL)-23/IL-12 and supports T helper cell type 1 (Th1) responses, whereas Mphi-2 fails to produce IL-23/IL-12, predominantly secretes IL-10, and inhibits Th1 function. Here, we further describe the phenotypic and functional profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
310
2
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 351 publications
(356 citation statements)
references
References 41 publications
36
310
2
8
Order By: Relevance
“…By contrast, the expression of markers related to M2 macrophage activation, such as CD16, CD163, MerTK, CD206, AMAC1 and CD200R1 [23][24][25][26][27], was upregulated in cmMTB-conditioned cells ( Figure 1B, Supplementary information, Figure S1B). Similarly, the expression of CCR2 and CCR5 chemokine receptors was higher in the presence of cmMTB, supporting the acquisition of the M2 program (Supplementary information, Figure S1C) [28,29]. More precisely, the expression of M2 markers was specifically augmented within CD16 + population compared with the CD16 − counterpart, with a higher increase of CD163 and CD206 upon cmMTB treatment monocytes ( Figure 1C).…”
Section: Differentiation Of Human Monocytes Towards An M2-like Activasupporting
confidence: 51%
See 1 more Smart Citation
“…By contrast, the expression of markers related to M2 macrophage activation, such as CD16, CD163, MerTK, CD206, AMAC1 and CD200R1 [23][24][25][26][27], was upregulated in cmMTB-conditioned cells ( Figure 1B, Supplementary information, Figure S1B). Similarly, the expression of CCR2 and CCR5 chemokine receptors was higher in the presence of cmMTB, supporting the acquisition of the M2 program (Supplementary information, Figure S1C) [28,29]. More precisely, the expression of M2 markers was specifically augmented within CD16 + population compared with the CD16 − counterpart, with a higher increase of CD163 and CD206 upon cmMTB treatment monocytes ( Figure 1C).…”
Section: Differentiation Of Human Monocytes Towards An M2-like Activasupporting
confidence: 51%
“…Here we found that migration in Matrigel is mainly based on chemoattraction mediated by recombinant CCL5 but not CCL2 or CCL4 (Supplementary information, Figure S6E). Despite the fact that the expression of CCR2 and CCR5 was enhanced by cmMTB (Supplementary information, Figure S1C), and that their different chemokine ligands are strongly secreted by Mtb-infected macrophages [29,34], the depletion of CCL2, CCL4 and CCL5 from cmMTB did not significantly alter their migration properties (Supplementary information, Figure S6F). Since the activation program of macrophages modulates their 3D migration capacities [49], we hypothesized that the enhanced cell motility in response to cmMTB might result from the acquisition of the M2-like phenotype.…”
Section: The Cd16 + Cd163 + Mertk + Pstat3 + Monocyte-macrophages Dismentioning
confidence: 99%
“…Of interest, this profile appeared to be more pronounced in patients with peripheral arthritis than in those with pure axial SpA (26). Based on the fact that IFN␥ is an important determinant of M1 polarization (2,3,(20)(21)(22) and on the association of synovial CD163ϩ M2 macrophages, but not T lymphocytes, with disease activity in peripheral SpA (9), the present study examined in more detail whether the presence of distinct macrophage subsets in both diseases is associated with different local inflammatory milieus.…”
Section: Discussionmentioning
confidence: 87%
“…M1 macrophages secrete large amounts of the key proinflammatory cytokines TNF␣ and IL-1␤ (20). Despite the similar degree of global joint inflammation, the SF levels of TNF␣ (mean Ϯ SEM 5.9 Ϯ 1.3 pg/ml versus 19.9 Ϯ 4.4 pg/ml; P ϭ 0.005) ( Figure 2D) and IL-1␤ (mean Ϯ SEM 3.2 Ϯ 1.0 pg/ml versus 24.1 Ϯ 5.3 pg/ml; P Ͻ 0.001) ( Figure 2E) were markedly lower in SpA than RA.…”
Section: Similar Levels Of Local Inflammation In Ra Versusmentioning
confidence: 99%
“…25 We further examined the expression of pattern recognition receptors involved in DV-induced inflammatory cytokine releases, such as Toll-like receptors (TLRs), [26][27][28] …”
Section: Differential Phenotypes Of Gm-m and M-mmentioning
confidence: 99%